Art is not what you think it is - Preziosi, Donald, 1941- (John Wiley & Sons, 2012)
Art Is Not What You Think It Is utilizes original research to present a series of critical incursions into the current state of debate on the idea of art, making manifest what has been largely missing or unsaid in those discussions. Links museology, history, theory, and criticism to the realities of contemporary social conditions and shows how they have structurally functioned in a variety of contexts. Deals with divisive and controversial problems such as blasphemy and idolatry, and the problem of artistic truth. Addresses relations between European notions about art and artifice and those develop.